Two-Dimensional Numerical Study of the Transient Flow Conditions in Complete Shock Tunnel - Mohsen A.M.; Yusoff M.Z.; Sultan Aljibori H.S.; Al-Falahi A.; Kadhum A.A.H. (Shahid Chamran University of Ahvaz, 2023)
In the current research, an axisymmetric model is developed to study high-speed unsteady flow in the test section of a 7 meter-long shock tunnel. The computational calculations of the shock tunnel are conducted using the Fluent CFD solver. The Finite Volume Method (FVM) is used to discretize the governing equations of mass, momentum, and energy. The accuracy of the numerical model is investigated with first-order upwind, second-order upwind, and third-order MUSCL schemes. Adaptive mesh refinement is implemented to resolve the shock wave and contact surface regions accurately. The numerical results are compared with theoretical calculations and experimental data from experimental tests and the comparison shows good agreement.Different test gases of Helium, Air and CO2, are utilized in the current study. The results show that steady test conditions are maintained for a longer test time by adjusting the pressure ratio and gas combination across the diaphragm. The highest shock wave speed and strength are achieved for a gas combination of Helium-CO2, but a longer test duration is observed when using Air as the test gas. 2021 Published by Shahid Chamran University of Ahvaz